Analysis of the Clinical Characteristics and Pituitary Function of Patients in Central China With Rathke’s Cleft Cysts - Zhang, Lixia; Li, Xueyuan; Li, Chong; Wang, Zhifang; Zheng, Lili; Qin, Guijun; Wang, Shoujun; Xu, Lijun (Frontiers in Endocrinology, 2022)
Objective A Rathke’s cleft cyst (RCC) is a common, benign, cystic disease that often leads to hypophyseal dysfunction or head symptoms. The relationship between RCCs and pituitary gland function is not clear. We therefore carried out a study to examine this relationship in greater detail. Methods The study was a retrospective, cohort design in patients diagnosed with a RCC between January 2019 to July 2021 at the First Affiliated Hospital of Zhengzhou University, China. Results A total of 221 patients were enrolled and then divided into study cohorts according to the diameter of the RCC, clinical manifestations, and surgical treatment received. The majority of patients were symptomatic (143/221), including 83 cases of dizziness and headache, 9 of vision loss and visual field defect, and 2 of diabetes insipidus. 52 cases had abnormal pituitary function, with 8 cases interestingly showing high adrenocorticotropic-hormone (ACTH) and cortisone levels, while 8 juvenile cases had developed central precocious puberty. Patients with larger RCCs were more likely to present with headaches and dizziness, with subjects who suffered from these symptoms having high ACTH and cortisone levels. Conclusion Although the size of a RCC is not an important factor influencing hypopituitary function, we consider that endocrine evaluation should be carried out in all patients with a RCC.